PENGARUH PHENOMENON-BASED LEARNING PADA PEMBELAJARAN IPAS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SDN 24 PARUPUK TABING KOTA PADANG - Azmi, Rulvita; Meizatri, Ranti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the use of less innovative learning models, which leads to student boredom and difficulties in understanding the material being taught. This occurs because the learning process tends to emphasize memorization rather than meaningful understanding, and students are accustomed to receiving information without going through a process of discovery. As a result, students are less able to develop their thinking patterns, construct ideas, and enhance their critical thinking skills.The purpose of this study is to examine the effect of the Phenomenon-Based Learning model on the critical thinking skills of fourth-grade students. This research employs a quasi-experimental design with a non-equivalent control group design. The population of this study consists of all students in the selected classes, and the sampling technique used is total sampling, in which the entire population is used as the research sample, consisting of 24 students in the experimental class and 27 students in the control class. The instrument used in this study is a multiple-choice test.Based on the results of the study, the average posttest score of the experimental class was higher, at 78.54, compared to 69.63 in the control class. After conducting hypothesis testing using an independent sample t-test, the significance value (2-tailed) was found to be 0.001 < 0.05. Therefore, H₀ is rejected and Hₐ is accepted, indicating that there is a significant effect of the Phenomenon-Based Learning model on students’ critical thinking skills.